Isolation and characterization of cyclo-(tryptophanyl-prolyl) and chloramphenicol from Streptomyces sp. SUK 25 with antimethicillin-resistant Staphylococcus aureus activity - Alshaibani MM; Jalil J; Sidik NM; Edrada-Ebel R; Zin NM (Dove Medical Press, 2016)
Muhanna M Alshaibani,1 Juriyati Jalil,2 Nik M Sidik,3 Ruangelie Edrada-Ebel,4 Noraziah M Zin1 1Programme of Biomedical Science, School of Diagnostic and Applied Health Sciences, Faculty of Health Sciences, 2Drug and Herbal Research Centre, Faculty of Pharmacy, Universiti Kebangsaan Malaysia, Kuala Lumpur, 3School of Bioscience and Biotechnology, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, Bangi, Malaysia; 4Strathclyde Institute of Pharmacy and Biomedical Sciences, University of Strathclyde, Glasgow, Scotland Background: Zingiber spectabile, commonly known as Beehive Ginger, is used as an ethnobotanical plant in many countries as an appetizer or to treat stomachache, toothache, muscle sprain, and as a cure for swelling, sores and cuts. This is the first report of isolation of Streptomyces strain from the root of this plant. Strain Universiti Kebangsaan 25 (SUK 25) has a very high activity to produce secondary metabolites against methicillin-resistant Staphylococcus aureus (MRSA), which is associated with high morbidity and mortality rates due to acquired multidrug resistance genes and causes medication failure in some clinical cases worldwide. Phylogenetic analysis based on the 16S ribosomal RNA gene sequence exhibited that the most closely related strain was Streptomyces omiyaensis NBRC 13449T (99.0% similarity). Aim: This study was conducted to carry out the extraction, identification, and biological evaluation of active metabolites isolated from SUK 25 against three MRSA strains, namely, MRSA ATCC 43300, MRSA ATCC 33591, and MRSA ATCC 49476. Materials and methods: The production of secondary metabolites by this strain was optimized through Thronton’s media. Isolation, purification, and identification of the bioactive compounds were carried out using reversed-phase high-performance liquid chromatography, high-resolution mass spectrometry, Fourier transform infrared, and one-dimensional and two-dimensional nuclear magnetic resonance. Results: During screening procedure, SUK 25 exhibited good antimicrobial potential against several strains of MRSA. The best biological activity was shown from fraction number VII and its subfractions F2 and F3 with minimum inhibitory concentration values at 16 µg/mL and 8 µg/mL, respectively. These two subfractions were identified as diketopiperazine cyclo-(tryptophanyl-prolyl) and chloramphenicol. Conclusion: On the basis of obtained results, SUK 25 isolated from Z. spectabile can be regarded as a new valuable source to produce secondary metabolites against bacteria, especially MRSA. Keywords: Zingiber spectabile, MRSA, SUK 25, cyclo-(tryptophanyl-prolyl), chloramphenicol, HR-MS, NMR